Chronic viral coinfections differentially affect the likelihood of developing long COVID - Michael J. Peluso; Tyler‐Marie Deveau; Sadie E. Munter; Dylan Ryder; Amanda M. Buck; Gabriele Beck‐Engeser; Fay Chan; Scott Lu; Sarah A. Goldberg; Rebecca Hoh; Viva Tai; Leonel Torres; et al. (2022)
BACKGROUND. The presence and reactivation of chronic viral infections, such as EBV, CMV, and HIV, have been proposed as potential contributors to long COVID (LC), but studies in well-characterized postacute cohorts of individuals with COVID-19 over a longer time course consistent with current case definitions of LC are limited.